PREACHING WHEN VIRAL THREATS CONVERGE: USA SERMONS, 31 MAY AND 7 JUNE 2020 - Brown, S.A. (Acta Theologica, 2020)
How is God present and active in this time and place? This question has been a pressing one for preachers and congregations amid the COVID-19 pandemic and its impacts. In the USA, the urgency of this theological question intensified when nationwide protests erupted following the release, on 26 May, of the video of the death of George Floyd. Floyd, an unarmed Black man, died pleading for breath, his neck pinned to the pavement by a police officer’s knee. Sermons preached in the USA in congregations of distinctive predominant racial identity on the two Sundays following Floyd’s death (31 May and 7 June 2020) are assessed hermeneutically, asking: “In what ways did US sermons, preached on 31 May and 7 June 2020, interpret divine presence and activity in relation to the preacher’s interpretation of listeners’ needs and responsibilities; biblical text(s) referenced, and/or the dual public crisis impinging on national life?”